Fluorometric and Docking Analysis of the Complex Formation between an Anti-Cancer Drug, Chlorambucil and Bovine Serum Albumin - Saufi, Aimi Nabila Mohamad; Ridzwan, Nor Farrah Wahidah; Mohamad, Saharuddin; Tayyab, Saad; Abd Halim, Adyani Azizah (Association of Pharmaceutical Teachers of India, 2019)
Background: To characterize the interaction between chlorambucil (CHB) and the carrier protein, bovine serum albumin (BSA) in order to understand the transport of this drug in blood circulation. Methods: Fluorescence quenching titration method was used to examine the interaction of CHB with BSA by determining its binding constant and binding stoichiometry. The binding site identification was probed with molecular docking techniques. Results: Values of the Stern-Volmer constant (KSV), bimolecular quenching rate constant (kq)and binding constant (K) for CHB-BSA system were determined a as 3.57×104 M−1, 5.67 × 1012 M−1 s−1 and 5.58 × 104 M−1, respectively. Binding stoichiometry was found to be ~1.0, as obtained from the double logarithmic plot. The molecular docking results revealed that CHB binds to both Site I and Site II of BSA, however Site II was predicted to be the preferred binding site. Conclusion: The value of Ka suggested intermediate binding affinity between CHB and BSA with the binding stoichiometry of 1:1. CHB was found to have the binding preference at Site II of BSA due to formation of greater contacts. © 2019, Association of Pharmaceutical Teachers of India. All rights reserved.